2015
DOI: 10.1016/j.eururo.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Predicting Prostate Cancer–specific Mortality for Men with Biochemical Recurrence After Radical Prostatectomy

Abstract: Background The natural history of prostate-specific antigen (PSA)-defined biochemical recurrence (BCR) of prostate cancer (PCa) after definitive local therapy is highly variable. Validated prediction models for PCa-specific mortality (PCSM) in this population are needed for treatment decision-making and clinical trial design. Objective To develop and validate a nomogram to predict the probability of PCSM from the time of BCR among men with rising PSA levels after radical prostatectomy. Design, setting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 37 publications
6
161
1
1
Order By: Relevance
“…In addition to the shorter postoperative survivals, patients with very high-risk PCa had significantly earlier clinical progression and PCSM from the time of BCR, which is consistent with previous reports showing a significant association between shorter time to BCR and post-BCR clinical progression (25,26) or PCSM (27)(28)(29). However, our subclassification is clearly different from previously proposed ones in that it provides predictive information preoperatively, which yields strong advantages as described above.…”
Section: Discussioncontrasting
confidence: 49%
“…In addition to the shorter postoperative survivals, patients with very high-risk PCa had significantly earlier clinical progression and PCSM from the time of BCR, which is consistent with previous reports showing a significant association between shorter time to BCR and post-BCR clinical progression (25,26) or PCSM (27)(28)(29). However, our subclassification is clearly different from previously proposed ones in that it provides predictive information preoperatively, which yields strong advantages as described above.…”
Section: Discussioncontrasting
confidence: 49%
“…On the other hand, regarding oncological outcomes, other single-institution experiences of RARP including several surgeons' experiences found that EPE and PSM were less likely to be found in patients with large prostates [4]. The tumor's EPE and PSM are well-established prognostic factors that impact BCR and long-term survival after radical prostatectomy [15][16][17][18][19]. In their RARP series, Skolarus et al [20] also reported that patients with an enlarged prostate had lower PSMs and Gleason scores.…”
Section: Discussionmentioning
confidence: 92%
“…Locally advanced disease includes extracapsular extension (ECE), seminal vesicle invasion (SVI) or local pelvic structures, whereas distant disease reflects lymph node involvement (LNI), bone or visceral organ metastasis [73][74][75]. Predictive staging nomograms allow the urologist to prognosticate clinical outcomes for the patient [76]. The Partin tables are the classic algorithm that combines clinical stage, preoperative serum PSA and biopsy Gleason grade to predict pathological stage.…”
Section: Nomograms For Stagingmentioning
confidence: 99%